PTU-105 Real world effectiveness, safety and cost per cure in hepatitis C patients treated with protease inibitor based therapy: results from the HCV research UK cohort. (22nd June 2015) - Barclay, S; Cooke, G; Irving, W; Holtham, E; Bec, M; Schwarzbard, J
Abstract : Introduction: To estimate real world effectiveness, safety and cost per sustained virological response (SVR) of 1 st generation protease inhibitor (PI)- based therapies for GT1 chronic HCV infection (CHC) in clinical practice in the UK. Method: Patients treated with telaprevir (TPV) or boceprevir (BOC) (stratified 2:1), pegylated interferon and ribavirin (PR) with available outcome data were randomly selected from the HCV Research UK database. Healthcare utilisation and adverse events (AEs) requiring intervention were identified from case note review. Cost of drugs, visits, diagnostics, and AE management were estimated from published sources. Causality of treatment regimen in relation to AE was independently assessed by 2 clinicians. Cost per SVR was calculated as total median cost divided by SVR rate. Sensitivity analyses exploring the impact of SVR rate, discontinuations, inclusion of unclassifiable AEs/hospitalisations and PI price on cost per SVR were undertaken. Results: 154 patients from 35 UK centres were analysed. Baseline characteristics: median age 50y (IQR 44–56), male 73%, cirrhotic 21%, 52% treatment experienced (TE). Overall SVR was 62.3% (range 25% in cirrhotic prior null responders, to 86.2% in non-cirrhotic prior relapsers). 53/154 (34.4%) patients discontinued therapy prematurely (50.9% physician withdrew, 26.4% patient withdrew, 22.6% failed stopping rules). 36% (55/154) experienced treatment-related AEs requiring intervention, leading to treatment discontinuation in 25.4% (14/55). 8.4% (13/154) patients required hospitalisation for treatment related AEs. Total treatment related costs for cohort were £4, 288, 802 (PI: 68.3%, PR: 26.3%, AE management and follow-up: 5.4%). Median total cost per cure was £44, 852 (range £35, 492 TN non-cirrhotic to £107, 288 in cirrhotic prior NR). Conclusion: This is the first UK multicentre study estimating outcomes and costs of PI based regimen in clinical practice. There was substantial variation in SVR and cost per SVR among patient subgroups. These cost per SVR estimates are conservative as retreatment costs for patients not achieving SVR are not included. The high discontinuation rate and HCV treatment-related AEs and hospitalisations suggest a substantial additional burden. Disclosure of interest: S. Barclay Grant/ Research Support from: Gilead, Janssen, MSD, Consultant for: Abbvie, BMS, Gilead, Janssen, MSD, Speaker Bureau of: Gilead, Janssen, MSD, Roche, G. Cooke Grant/ Research Support from: Janssen, BMS and Gilead, Consultant for: Janssen, BI, Gilead and Merck, W. Irving Grant/ Research Support from: Pfizer, GSK, Gilead; Educational grants: BI, Gilead, Merck, Consultant for: Merk, Novartis, BMS, Speaker Bureau of: Janssen, E. Holtham: None Declared, M. Bec Conflict with: conducted the statistical analyses funded by Gilead, J. Schwarzbard Conflict with: conducted the statistical analyses funded by Gilead.